New Media Research Project - Acheson, Kim; Mezera, Kailey; Sukowatey, Laura; You, Jenny (My University, 2010)
The goal of the new media project was to investigate media use by college students at the University of Wisconsin--Eau Claire in relation to entertainment events in and around the University. This was done by administering two surveys to University students. Both surveys indicated how University students learn about entertainment news and events in and around the University by dividing the media into the categories of newspaper, television, radio, and the current University online news site, and by age group.
Color poster with text and graphs.
Keywords: Entertainment events--Advertising; Publicity--Technological innovations; Mass media and publicity; Mass media and youth; College students--Conduct of life; Posters